PROTECTION OF HUMAN RIGHTS FOR WORKERS IN THE JOB CREATION LAW FROM AN ISLAMIC LEGAL PERSPECTIVE - Yusila, Anggina; Andatu, Mabruri; Fatimatuzzahra; Alamsyah, Sal Sabila (DE'RECHTSSTAAT, 2024)
This research is motivated by human rights issues that often occur in carrying out work to meet economic needs. However, this is regulated in the Job Creation Law which was passed in 2020 considering the protection of Human Rights (HAM) for workers. This study aims to determine and analyze the Protection of Human Rights for Workers in the Job Creation Law from an Islamic Law Perspective. The research methodology used is literature research (library research) involving analysis of primary and secondary legal materials. The results of the study show that although the Job Creation Law includes elements of protection such as PKWT compensation and social security, its implementation still faces several problems, such as limited supervision and bias towards employers. The Islamic law perspective emphasizes fair treatment and justice for workers, which can be used as a reference to improve the protection of human rights in employment. Strict supervision and strengthening of regulations in line with the principles of social justice and human rights must be used to improve the protection of workers' rights.